The Fun Approach to English Learning - Camargo V. Nancy Idaly; Lacer Bernice (Universidad Nacional de Colombia, 2001)
This project was conducted in order to improve oral interaction in English through the practice of games that permit the development of communication. This provided us the
opportunity to improve our methodology and to encourage 4th grades, at the Henao y Arrubla Institute. At the end of this investigation, we observed that not only the sample had improved their oral production, but the rest of the students could interact in the process as well